SMART SOLUTION FOR OPTIMIZED MASS CUSTOMIZATION PROCESS IN SMART PHONE INDUSTRY: Received: 03rd September 2022; Revised: 19th December 2022, 25th December 2022; Accepted: 18th January 2023 - Dixit, Abhinav; Dixit, Ankita; Kaur, Harpreet; Singh, Jaideep; Guleri, Karan (PEOPLE: International Journal of Social Sciences, 2023)
The concept of mass customization envisages a firm pursuing differentiation vis-à-vis its competitors in the form of its customized solutions to the consumers, and at the same time adopting cost-effective measures to bring down the cost of production of those solutions. Mass customization has proved to be a path-breaking approach in many industries like fashion, footwear and computer. In this paper, we aim to cover the possibilities of mass customization in the smartphone industry at the hardware, software as well as OS level. We will also cover how, by implementing mass customization, smartphone companies can save costs of finished goods inventories, and at the same time, increase consumers’ willingness to pay by providing them with customized solutions. This paper proposes a smart solution for implementing mass customization through mathematical formulation and aims to detect the optimized groups and cost estimation.